The Effectiveness of Various Types of Local Hydromacrophytes on The Phytoremediation Process of Catfish Pond Wastewater using a Batch Culture System : The Effectiveness of Various Types of Local Hydromacrophytes - Umi Sa'adah; Dian Siswanto; Catur Retnaningdyah (Journal of Tropical Life Science, 2023)
This study aimed to determine the effectivity of various types of local hydromacrophytes on the remediation of wastewater from catfish culture ponds in Gondosuli village, Gondang, Tulungagung, East Java, Indonesia, using a batch culture system. This experiment used a completely random design and was conducted in the glasshouse. The batch culture system was conducted in a 30 L tank containing sand and gravel as the medium for hydromacrophytes. This research consisted of five treatments (emergent, submerged, floating leaf, polyculture of 3 types of hydromacrophytes, and control without hydromacrophytes). This study was repeated three times at the same time. The effectiveness of the phytoremediation model was monitored using indicators of water physicochemical parameters and the biotic index of phytoplankton. The biotic indices were used the Shannon-Wiener diversity index (H') of phytoplankton and the diatom biotic index (Trophic Diatom Index (TDI) and Percentage of Pollution Tolerant Value (%PTV)). After giving the treatment, monitoring was carried out on days 0, 10, 20, 30, and 40. The results showed that the batch culture system for phytoremediation post-harvest catfish pond wastewater with local hydromacrophytes improved the water quality. However, not all water physicochemical parameters after treatments meet Indonesian water quality standards. Abundance showed water quality fluctuations over time, while Shannon Wiener's diversity index (H' value) decreased as water quality decreased. This study's PTV value demonstrated that pollutant levels vary by treatment. Only the control and submerged hydromacrophytes improved their TDI status; another treatment remained moderate. The best treatment was 40 days after acclimatization with polyculture treatment of three types of local hydromacrophytes. Research and other systems like continuous culture are needed for optimal results to improve water quality.